Students' Mathematical Problem Solving Ability in Arithmetic Rows and Sequences in Grade VIII Junior High School - Felma Jesicha Kakumboti; Derel F. Kaunang; Jorry M. Monoarfa (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to evaluate the mathematical problem-solving ability of eighth grade students of SMP Negeri 1 Bitung. This study is qualitative. The research methodology includes the planning stage, the implementation stage, and the data analysis stage. The selection of research volunteers was carried out by grouping them into three ability categories: high, medium, and low. Information on students' mathematical problem-solving abilities was obtained through exam results and interviews. The verification of the validity of the data used was technical triangulation. The findings of this study indicate that high-ability students are comprehensively involved in the problem-solving stages described by Polya, namely by effectively executing the process of understanding the problem, formulating the plan, implementing the plan, and verifying it. Medium-ability students did not complete the problem-solving stages described by Polya, because they were only able to understand the problem and verify the solution. Low-ability students did not complete the problem-solving stages described by Polya, especially not being able to understand the problem, not being able to formulate a plan, being able to execute the plan, and not being able to verify the solution.